Developing Public Service Announcements to Help Prevent Suicide among Young People - Ftanou, Maria (Int J Environ Res Public Health, 2021)
Background: Suicide is the leading cause of death among young people in Australia. Media campaigns have the potential to reach a broad audience, change attitudes and behaviours, and, ultimately, help prevent suicide. Little is known about the type of content or format suicide prevention media message should take to help prevent suicide among young people. Objective: the objective of this study was to involve young people aged 18 to 24 years in developing three suicide prevention public service announcement (PSAs) targeting young people at risk of suicide appropriate for testing in a randomised controlled trial (RCT). Method: fifteen young people attended at least one of four workshops in Melbourne, Australia. The workshops focused on exploring the appropriateness of three key suicide prevention media PSAs: “Talk to someone”, “Find what works for you”, and “Life can get better”. Young people also provided input into message content, format, and design. Results: participants perceived that all three suicide prevention PSAs were useful and helpful. Participants were concerned that the PSAs may not be suitable for nonwestern cultural groups, could trivialise psychological suffering, and that the actions they promoted could seem distant or unattainable to young people at risk. The featuring of young people, especially young people with hopeful narratives of how they overcame a suicidal crisis, was considered to be an important characteristic of suicide prevention PSAs targeting young people. Conclusions: Developing suicide prevention PSAs with young people is rare but essential to better understand young people’s needs and improve the quality of suicide prevention media PSAs. Further research is needed to evaluate the impact of suicide prevention PSAs developed by young people, for young people.